The impact of diet on gastroesophageal reflux disease in patients at an early age - Marzena Agnieszka Humańska; Agata Ulenberg; Ktarzyna Betke; Grzegorz Ulenberg; Danuta Ponczek; Agnieszka Pluta; Monika Kowlaska; Miroslawa Felsmann (Kazimierz Wielki University, 2018)
Admission: Reflex disease is one of the most common diseases of the upper gastrointestinal tract. In the conservative treatment, non-pharmacological primary role proper nutrition and diet compliance. Objective: The aim of the study was to determine the impact diet has on reflux disease. Material and methods:The study has been given to people with gastroesophageal reflux disease. The study was conducted in Bydgoszcz and Wloclawek. The study used a survey of their own design on socio-demographic data and questions about dietary treatment. Statistical analysis was performed using SPSS statistical program. Results:The highest percentage of women-study group accounted for 58.1%, while men accounted for more than 41.9% of the study population. The study was dominated by two age groups. People aged 45-59 years - 34.9%, and 60-74 years - 30.2%. Respondents most frequently observed symptoms of gastroesophageal reflux disease after eating high-fat products - 34.9%. 7 persons adversely affected by the sharp spices, for 6 people - chocolate, for more than 10% of soda. For nearly half of the study population (44.2%) diet was too cumbersome to be able to be used. 10 people (23.3%) is not made trouble, 18.6% of respondents are aware that some products hurt them, but they can not give them up, and 14% of respondents often forgot about the use of supplements. Conclusions: 1. The symptoms of gastroesophageal reflux disease in subjects most often occur after eating high fat products. 2. The incidence of GERD increases with age. 3. For almost half of the population studied diet is too cumbersome to be able to use it. 4. Addictions such as alcohol and smoking have an impact on the incidence of gastroesophageal reflux disease.